2010
DOI: 10.1603/ec10010
|View full text |Cite
|
Sign up to set email alerts
|

Bottom-Up Effect of Different Host Plants on Plutella xylostella (Lepidoptera: Plutellidae): A Life-Table Study on Canola

Abstract: The effects of 10 commercial canola, Brassica napus L., cultivars widely grown in Iran--'SLM(046),' 'Opera,' 'Okapi,' 'RGS(003),' 'Modena,' 'Sarigol,' 'Zarfam,' 'Licord,' 'Hayula(420),' and 'Talaye'--on the demographic parameters of diamondback moth, Plutella xylostella L. (Lepidoptera-Plutellidae), were determined. The experiments were conducted in a growth chamber at 25 +/- 1 degrees C, 65 +/- 2% RH, and a photoperiod of 16:8 (L:D) h. The comparison of intrinsic rate of natural increase (r(m)), net reproduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 40 publications
2
26
2
Order By: Relevance
“…The r of B. macroscopa was similar to several noctuid species, e.g ., in Helicoverpa armigera it was 0.115 to 0.142 days −1 and 0.171 to 0.264 days −1 in Spodoptera exigua (Hübner) 19,30 , but the R 0 values were less than those in H. armigera (177.3 to 270.1 eggs) and S. exigua (126.4 to 377.1 eggs) 17,30 . The r value of B. macroscopa was smaller than that reported for P. xylostella which exceeded 0.2 days −1   31,32 . The R 0 of P. xylostella differed significantly on various host plants ranging from 30.6 to 183.8 eggs 31,32 .…”
Section: Discussioncontrasting
confidence: 70%
“…The r of B. macroscopa was similar to several noctuid species, e.g ., in Helicoverpa armigera it was 0.115 to 0.142 days −1 and 0.171 to 0.264 days −1 in Spodoptera exigua (Hübner) 19,30 , but the R 0 values were less than those in H. armigera (177.3 to 270.1 eggs) and S. exigua (126.4 to 377.1 eggs) 17,30 . The r value of B. macroscopa was smaller than that reported for P. xylostella which exceeded 0.2 days −1   31,32 . The R 0 of P. xylostella differed significantly on various host plants ranging from 30.6 to 183.8 eggs 31,32 .…”
Section: Discussioncontrasting
confidence: 70%
“…Intrinsic rate of increase "r" is the most useful demographic parameter for contrasting the compatibility of populations across various weather and food resource conditions (such as cardenolids, glucosinolate, waxes, plant volatiles, leaf morphology or all of these factors ) (Smith 1991;Soufbaf et al 2010aSoufbaf et al , b, 2012Goodarzi et al 2015). Comparison of the intrinsic rate of increase often provides considerable insight in evaluating host plant suitability to herbivorous arthropods in integrated pest management programs (Fathipour & Sedaratian 2013;Rezaie et al 2013;Ahmad & Shafiq Ansari 2014;Goodarzi et al 2015).…”
Section: Biological Parametersmentioning
confidence: 99%
“…Plants may mediate many of the interactions between herbivores and their parasitoids, influencing the preference and performance of parasitoids (Cortesero et al 2000;Karimzadeh et al 2013). Generally, in a tritrophic system variation in host-plant characteristics (Soufbaf et al 2010a(Soufbaf et al , 2010bSoufbaf et al 2013) may have differential effects on a herbivore and its associated natural enemies (Karimzadeh & Wright 2008). Many studies revealed that different host-plant species or cultivars have differential effects on P. xylostella parasitism success by parasitoids, in particular, Cotesia vestalis (Haliday) and Diadegma semiclausum (Hellen) (e.g.…”
Section: Introductionmentioning
confidence: 99%